Community Empowerment Through Synbiotic Feed Technology Innovation in The Poultry Industry to Support Productivity and Food Safety - Dwinhoven, Ifhan; Relatami, Andi N Renita; Syamsurya, Fajar; Firman, Sri Wahyuni; Sudirman, Andi Aridhasari; Sudirman, Andi; Mubarak Z, Sultan; Tassaka, Asmi Citra Malina A.R.; Rahmi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The poultry farming industry is part of the growing agro-complex sector and is essential in providing animal protein to support national food security. The productivity and safety of the food produced are still challenging in cultivation activities. The Socialization of Poultry Farming Management and Training on Making Independent Synbiotic Feed based on ODB bacteria from PT Pertamina Patra Niaga AFT Hasanuddin oil Cather is a community empowerment activity that has an impact on the beneficiary community, namely the Lelang Kassie farmer women's group and the Baji Mangai Village community, Maros Regency. This activity includes socialization, training, and application of technology in duck farming activities. Increased knowledge and skills of the community can independently produce ODB bacterial starter, which is then used in synbiotic feed and applied to poultry. This has an impact on the potential for increasing community income, and this innovation can encourage an increase in duck production with the quality of meat and eggs produced safe from chemical residues. Contribution to Sustainable Development Goals (SDGs):SDG 1: No povertySDG 2: Zero hungerSDG 3: Good health and well-beingSDG 12: Responsible consumption and productionSDG 15: Life on Land